The Role of Creative Communities in Supporting Development of Urban Heritage Tourism Kota Tua Jakarta - Armitawati, Istiqomah (GoAcademica Research & Publishing, 2024)
Kota Tua Jakarta or Jakarta’s Old City is a Cultural Heritage Area as well as a National Vital Object. This area is managed by the DKI Jakarta Provincial Government as a historical tourist destination. The increase in tourist visits to this area is caused by various things, one of which is the existence of tourist attractions developed by the local creative community. The role of the creative community has not been identified thoroughly. This study aims to explain the role of the creative community as a supporting tourist attraction in Kota Tua area. In addition, identifying this role is also important to help the government plan regulations that have an impact on optimizing tourism potential. This study was conducted using a qualitative method with descriptive data presentation. The results of the study show that the creative community also plays a role in developing tourism in Kota Tua ​​Jakarta. The role of the creative community is not only in providing new experiences, but also in being able to enliven the attractive atmosphere in the area of ​​cultural heritage sites that have developed into tourist destinations. The creative community has also become a tourism identity in the Kota Tua ​​Jakarta, apart from the physical side of the interesting colonial-style building architecture.